Addressing silent hypoxemia with COVID-19: Implementation of an outpatient pulse oximetry program in Vermont - Marlowe Galbraith; Patsy Kelso; Mark Levine; Richard C. Wasserman; Jessica Sikka; Jennifer S. Read, MD, MS, MPH, DTM&H (Elsevier, 2021)
Objectives: We initiated an outpatient pulse oximetry program to facilitate more rapid detection of clinical deterioration of persons with COVID-19. Methods: Vermont residents in non-congregate settings with laboratory-confirmed SARS-CoV-2 infection were eligible for inclusion. Results: Acceptance of pulse oximetry occurred more frequently among those who were older or symptomatic, spoke English, or who had underlying medical conditions. Conclusions: We provide the first description of an outpatient pulse oximetry program for COVID-19 by a state health department in the U.S.